Warpage analysis on thick shell part using response surface methodology (RSM) and bat algorithm (BA) to optimize parameter setting in injection molding process - Ch'Ng, S. Q.; Nasir, S. M.; Fathullah, M.; Noriman, N. Z.; Mohd Sazli, Saad (AIP Publishing, 2018)
Injection molding is a common process to manufacture plastics parts with low cost. During Injection Molding Process (IMP), many types of defects would occurs on the plastics parts and affect its quality. Warpage one of the common types of defects and it is due to the differential shrinkage in plastics parts. Although warpage are difficult to avoid, but it can be reduced by various method such as Response Surface Methodology (RSM) and Bat Algorithm (BA). In order to reduce the warpage, this research focus on simulation and optimize the process parameters setting. Autodesk Moldflow Insight (AMI) 2012 software is used to simulate and determine the range of parameters setting that affect warpage on thick shell parts. RSM is use to optimize process parameters setting and reduce warpage problem during IMP by Design of Experiment (DOE) based on the recommended parameter setting in AMI. RSM also predict mathematical modelling and further used in BA. BA will optimize the process parameters setting and improve warpage value based on the results in AMI. Both RSM and BA are use to find the optimum IMP parameters to reduce warpage on the thick shell plastic parts. The recommended setting based on AMI shows that the warpage at X-axis is 0.6546 mm. After optimization, results at warpage X of RSM and BA had reduced to 0.5612 mm and 0.5279 mm respectively. RSM and BA optimization shows improvement of warpage by 14.27% and 19.36% respectively. The significance of this study is to minimize warpage during IMP and optimize the process parameter setting of injection molding by using RSM and BA. Plastic parts without warpage is beneficial to the industrial, because it will reduce cost consumption during assembly process and produce qualitative plastic products during IMP.